Konstruksi Pemikiran Yusuf Al-Qardhawi dan Sahal Mahfudh Tentang Pemberdayaan Ekonomi Masyarakat Berbasis Zakat Produktif - Maulida Khasanah (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Ineffectiveness of zakah as a means of poverty alleviation because its distribution is dominated by consumptive distribution, not productive distribution. This paper uses a qualitative approach in the form of desciptive-comparative research. Based on the synthesis-eclectic analysis, the construction’s thought of Yusuf al-Qardhawi and Sahal Mahfudh about economic community empowerment based on productive zakah as the findings of this paper are: First, productive zakah is a means to bridge the ideality of Islamic teachings that emphasize the economic prosperity with the reality of community moslems that face various economic problems. Second, the solution of economic problems based on “root of the problem” is through vocational training and funding as working capital; while the solution of zakah management problems based on “root of the problem” is through education of Sharia Zakah (Islamic law and ethics) and training of Zakah Management (professional and modern). Third, the implementing subjects involve systemic cooperation between Islamic scholars (‘ulama’), government (umara’) and society (ummah). Fourth, the objects in the form of working capital, work tools, vocational training and education. Fifth, the target is to increase the status of the recipient of zakah (mustahiq) to the giver of zakat (muzakki). Sixth, operational steps are based on POAC (Planning, Organizing, Actuating, Controlling) which is adheres to Islamic Sharia as well as modern disciplines. Keywords: Productive Zakah; Economic Empowerment; Yusuf al-Qardhawi; Sahal Mahfudh